Dermoid Cyst of the Pancreas: A Challenging Differential Diagnosis Among Benign Pancreatic Cysts - Milanetto, Anna Caterina; Moletta, Lucia; Liço, Valbona; Alaggio, Rita; Sperti, Cosimo; Pedrazzoli, Sergio; Pasquali, Claudio (JOP. Journal of the Pancreas, 2012)
Context Dermoid cysts are congenital developmental abnormalities of germ cell origin arising from embryonic residues and they are usually benign, well-differentiated lesions. They are commonly found in the ovary, testes and retroperitoneum; the pancreas is extremely rare as a primary site. Case report A 68-year-old woman presented a cystic lesion (4 cm) of the pancreatic tail as an incidental finding at a MR scan performed for other reasons. A CT scan confirmed the tail lesion, which had a lamellar calcification on the posterior wall. A 18FDG-PET was negative. Laboratory examination showed normal values, including CEA and CA 19-9. Because of the size of the lesion and the risk of malignancy, the patient underwent a spleen-preserving distal pancreatectomy. Histology showed a squamoid cyst (3 cm) of the pancreatic ducts. It was unilocular and had serous content and fibrous wall, with multilayered epithelium without cytological atypias (immunehistochemistry: CK7 positive and CK5 negative). The post-operative course was uneventful, but the patient was readmitted a few days after discharge for abdominal pain due to a peripancreatic fluid collection. She was treated with a percutaneous drainage and the catheter was removed after one month. She is still alive after 22 months of follow up. She is asymptomatic, with mild diabetes and a normal exocrine pancreatic function. The last CT scan and tumor markers were negative. Conclusion Less than 30 cases of dermoid cyst of the pancreas have been reported in the English literature. Most of patients were symptomatic by unspecific gastrointestinal discomfort. Imaging techniques failed the correct preoperative diagnosis, because the appearance may vary depending on the proportions of tissue components. They should be considered in the differential diagnosis of slow-growing benign pancreatic cysts. Despite the benign nature of dermoid cyst, oncologic resection is usually performed due to difficult preoperative diagnosis. No reliable predictive features were found to allow an organ- or parenchyma-preserving procedure. Surgery remains the treatment of choice to exclude malignancy.